Economic Prospects and Policy Challenges for the GCC Countries. (Policy Papers; Policy Paper, 2020)
The COVID-19 pandemic is having far-reaching consequences for the global economy. Measures to contain the spread of the virus have led to sharp declines in economic activity across the globe, particularly in 2020Q2. The hardest hit sectors have been those requiring intensive human contact, such as tourism, transportation, services, and construction, while, in general, IT-intensive activities have fared better. The economic contraction is most significant in advanced economies. The GCC countries face a double impact from the coronavirus and lower oil prices. GCC authorities have implemented a range of appropriate measures to mitigate the economic damage, including fiscal packages, relaxation of monetary and macroprudential rules, and the injection of liquidity into the banking system, and there are recent signs of improvement. Low oil prices have caused a sharp deterioration of external and fiscal balances, and fiscal strains are evident in countries with higher debt levels.